Faculty’s Portfolio Collaboration:To Enhance Student’s Placement through Faculty’s Coordination - Dontham, Rajesh; Yelpale, Sushant; Lokare, Varsha; Gavali, Pralhad; Patil, Manoj; Patil, Savita (Journal of Engineering Education Transformations, 2025)
This paper shares the best practices adapted in the department of Information Technology to enhance the employability of students. Student's placement is considered to be the most important factor for any program in the engineering education. The vision, mission, goals and curriculum of the Information Technology program are designed in-line to prepare the students to be industry ready. Also, the curriculum delivery and evaluation of students are designed and executed with a goal to prepare students to be industry ready. Though all the collaborative efforts of the work force of the IT department and its associates are taken to execute their tasks that should lead to placement of all eligible students, the placement statistics of the department is not satisfactory. The collaboration amongst the work force and its associates must be redefined to improve the placements of the students. To address the student's placements to its best, a team of volunteers from the faculty is formed under best practices activity of Quality Circle at RIT and proposed a solution by defining innovative practices that lead to the betterment of student's placement and titled as "Faculty's Portfolio Collaboration: To enhance Student's placement through faculty's coordination". The practices defined were practiced for one academic year and the results are analyzed. The analysis of the results showed that there is an improvement in the performance of students in most aspects and requires additional efforts for betterment of few other aspects. Necessary measures were also identified and suggested to faculties for the improvement in the portfolios that under performed. The practices defined will be continued in the department to achieve consistency in the results and analyze the same.